Estimation of dental age using Willems method and comparing it with Demirjian's method in 7-14-year-old children of Uttarakhand - Keerti Chandail; Varinder Goyal; Mehak Kaul; Satyam Dutt; Tishya Koul; Burhan Altaf Misgar (Wolters Kluwer Medknow Publications, 2022)
Age is one of the essential factors, which plays an important role in every aspect of life. Age is estimated on the basis of chronological age, bone age, dental age, mental age and others. This study represents the objective of an ideal age estimation technique to arrive at an age as close to the chronological age as possible. Aim: The aim of this comparative study was to estimate the dental age using Willems method by assessing the developmental stages of left seven permanent mandibular teeth in 7-14 years of age groups with the help of digital orthopantomogram and comparing it with Demirjian's method to conclude which method was more appropriate and better in Indian population of Uttarakhand region. Materials and Methods: A total of 100 digital orthopantomogram films of patients in the age group of 7-14 years was collected over the study period of 3 years from July 2014 to January 2017 and was equally distributed by convenience sampling. Group I included 50 boys and Group II included 50 girls aging 7-14 years of age (as permanent 7 teeth in the 3rd quadrant were to be assessed and scored according to the Demirjian's table, the 7-14 age group was selected). The date of birth of the subject was documented against their allocated identification number. Dental age according to Willem's method was calculated using Willem's table and Demirjian and Goldstein's table scores were used to calculate dental age by Demirjian's method. Results: Willems method was more accurate and better than Demirjian's method as it showed less mean percentage error, i.e., 0.34% as compared to 15.94% obtained from Demirjian's method in Group II and 2.19% as compared to 8.05% obtained from Demirjian's method in Group I. Conclusion: The results suggested that Willems method of dental age estimation was an effective method of age estimation and was better and more accurate than Demirjian's method.